2017
DOI: 10.1080/14767058.2017.1326902
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss among high-risk newborns admitted to a tertiary Neonatal Intensive Care Unit

Abstract: The prevalence of hearing loss is highest among high risk neonates and TEOAE and AABR were found to be reliable screening tools. Use of ototoxic drugs and mechanical ventilation for more than five days were significant risk factors for hearing loss in our study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
4
19
1
1
Order By: Relevance
“…In the study conducted by Khairy in 2017, sepsis was the risk factor for hearing loss in infants [7], but in the Alaee study, no correlation was found between sepsis and hearing loss [22]. This result is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the study conducted by Khairy in 2017, sepsis was the risk factor for hearing loss in infants [7], but in the Alaee study, no correlation was found between sepsis and hearing loss [22]. This result is consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Otoacoustic emission is a non-invasive, rapid, and appropriate method for assessing cochlear function. However, the diagnostic value of TEOAE alone is limited and ABR is more reliable for hearing screening [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their diagnosis is usually based on a combination of symptoms, laboratory parameters and clinical evaluations. Studies that show a significant association between sepsis or meningitis and hearing loss do not state the exact definition of diagnosis or the treatment guidelines . Diagnostic criteria and treatment regimens for sepsis and meningitis also typically vary across hospitals and settings, reducing the generalisation of these results .…”
Section: Discussionmentioning
confidence: 99%
“…Screening newborns for hearing impairment or hearing loss is important as this is one of the most frequent congenital conditions, affecting about 1-6 newborns per 1000 live births [1,2] with much higher rates among high-risk infants admitted to neonatal intensive care unit (NICU) [3]. In addition, about half of hearing impaired newborns have no known risk factors [1] highlighting the necessity to screen all newborns.…”
Section: Introductionmentioning
confidence: 99%